Hog meat and hoecake : food supply in the Old South, 1840-1860 - Hilliard, Sam Bowers (Southern Foodways Alliance studies in culture, people, and place., 2014)
When historical geographer Sam B. Hilliard's book Hog Meat and Hoecake was published in 1972, it was ahead of its time. It was one of the first scholarly examinations of the important role food played in a region's history, culture, and politics, and it has since become a landmark of foodways scholarship. In the book Hilliard examines the food supply, dietary habits, and agricultural choices of the antebellum American South, including Arkansas, Louisiana, Mississippi, Tennessee, Alabama, Georgia, North Carolina, and South Carolina. He explores the major southern food sources at the time, the r.